Embioptera (Insecta) from Brazil: New species and a taxonomic update - Szumik, Claudia Adriana (2022)
Eight new species of Embioptera from Brazil are described, diagnosed, and illustrated. For Anisembiidae: Chelicerca achilata Szumik, Pereyra & Juárez, sp. nov.; Saussurembia borba Szumik, Pereyra & Juárez, sp. nov. For Archembiidae: Archembia oruma Szumik, sp. nov.; Embolyntha oriximina Szumik, Pereyra & Juárez, sp. nov.; Pararhagadochir bonita Szumik, Pereyra & Juárez, sp. nov., Pararhagadochir marielleae Szumik, Pereyra & Juárez, sp. nov.; Pararhagadochir para Szumik, Pereyra & Juárez, sp. nov. For Clothodidae: Chromatoclothoda langa Szumik, Pereyra & Juárez, sp. nov. To clarify the higher classification of the Order and to have an accurate taxonomy, a species catalog and introduction to the four families present in Brazil is also detailed, including phylogenetic relationships, taxonomic actions, composition, distributions, and records maps. Herein, several taxonomic acts are proposed: (1) the synonymy of Chelicerca Ross (= Dactylocerca Ross confirmed junior synonym; = Schizembia Ross syn nov.; = Pelorembia Ross, confirmed junior synonym; = Cryptembia Ross, syn. nov.) and Saussurembia Davis (= Stenembia Ross, syn. nov.). (2) new status and delimitation for family Archembiidae Ross, stat. rev.; subfamily Archembiinae Ross, stat. rev.; subfamily Pachylembiinae stat. rev.; subfamily Scelembiinae stat. rev., and their genera included. (3) Diradius unicolor (Ross) (Teratembiidae) comb. nov., and (4) new locality records for previously cited species in the region.